Biochemical Characterization and Comparison of Two Closely Related Active mariner Transposases - Trubitsyna, Maryia (American Chemical Society, 2014)
[Image: see text] Most DNA transposons move from one genomic location to another by a cut-and-paste mechanism and are useful tools for genomic manipulations. Short inverted repeat (IR) DNA sequences marking each end of the transposon are recognized by a DNA transposase (encoded by the transposon itself). This enzyme cleaves the transposon ends and integrates them at a new genomic location. We report here a comparison of the biophysical and biochemical properties of two closely related and active mariner/Tc1 family DNA transposases: Mboumar-9 and Mos1. We compared the in vitro cleavage activities of the enzymes on their own IR sequences, as well as cross-recognition of their inverted repeat sequences. We found that, like Mos1, untagged recombinant Mboumar-9 transposase is a dimer and forms a stable complex with inverted repeat DNA in the presence of Mg(2+) ions. Mboumar-9 transposase cleaves its inverted repeat DNA in the manner observed for Mos1 transposase. There was minimal cross-recognition of IR sequences between Mos1 and Mboumar-9 transposases, despite these enzymes having 68% identical amino acid sequences. Transposases sharing common biophysical and biochemical properties, but retaining recognition specificity toward their own IR, are a promising platform for the design of chimeric transposases with predicted and improved sequence recognition.